mula sa "Baraha ni Baybayan: Mga Payo ni Agyu" - Acuna, (Tilde) Arbeen Regalado (Review of Women's Studies, 2023)
The hybrid work "mula sa 'Baraha ni Baybayan: Mga Payo ni Agyu'" incorporates ideas extracted from the deck of Tarot cards and the Ulahingan epic of the Livunganen-Arumanen Manobo. The Tarot and the Ulahingan integrate in both the visual and the textual aspect of the cards. Scenes during the Ilianon's construction of their fortress Nalandangan or Yendang correspond to the challenges during the journey of the Fool in the Tarot. Such a combination attempts to indigenize the universal and universalize the indigenous, through lines of art and poetry. As of the moment, the Major Arcana has been completed.